Renal transplant improves pulmonary hypertension in patients with end stage renal disease - Bozbas, Serife; Kanyilmaz, Suleyman; Akcay, Sule; Bozbas, Huseyin; Altin, Cihan; Karacaglar, Emir; Muderrisoglu, Haldun; Haberal, Mehmet (Multidisciplinary respiratory medicine, 2011)
Pulmonary hypertension (PH) is present in a significant proportion of patients with end stage renal disease (ESRD) and is of prognostic importance. Data on the effect of renal transplant on PH is very limited. In this study, the aim was to examine the effect of renal transplant on systolic pulmonary artery pressure (SPAP) determined by Doppler echocardiography. Analysis was performed on the records of 500 consecutive patients who underwent renal transplant at our center between the years 1999 to 2008. The prevalence of PH in the preoperative assessment period was established. Patients were diagnosed as having PH when measured SPAP values were > 35 mm Hg. Pulmonary hypertension was detected in 85 of the 500 (17%) patients under pre-transplant evaluation. At post-transplant follow up Doppler echocardiographic examination was performed on 50 of the 85 patients. After exclusion of 8 cases (1 due to massive pulmonary thromboemboli; 7 due to graft failure requiring dialysis therapy) analyses were performed on 42 patients who had undergone both pre- and post-transplant echocardiographic examination. Mean SPAP at pre-transplant evaluation was 45.9 ± 8.8 mm Hg and in 6 (14.3%) cases SPAP was above 50 mm Hg.Compared to pre-transplant values, a significant decrease was observed in mean SPAP values in an average of 53 months of postoperative follow up (41.8 ± 7.4 mm Hg vs. 45.9 ± 8.8 mm Hg, p < 0.0001). These findings indicate that patients with ESRD accompanied by PH may benefit from renal transplant. Further research is required for more concrete conclusions to be drawn on this subject.